Mass transport at electrodes of arbitrary geometry. Reversible charge transfer reactions in square wave voltammetry - Molina, A; Gonzalez, J; Laborda, E; Compton, R (2012)
The basis for mass transport of the electroactive species in different diffusion fields is examined, pointing out important insights in relation to the value of the surface concentrations for the case of fast electrode processes. Moreover, a general analytical solution for the transient current is given for several geometries, when an arbitrary sequence of potentials pulses is applied to macroelectrodes (planar), spheres, cylinders, discs and bands. The results are particularized for Square Wave Voltammetry. Explicit solutions for the net current and the forward and backward components are given. The effects of frequency, pulse amplitude and electrode size or shape on the peak current are studied. Moreover, the conditions for the attainment of the steady state response are analyzed in the different geometries as well as the characteristics of this response. © Pleiades Publishing, Ltd., 2012.